2019
DOI: 10.4315/0362-028x.jfp-18-553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Serovars, and Antimicrobial Resistance of Salmonella in Cecal Samples of Chickens Slaughtered in Pluck Shops in Trinidad

Abstract: The aim of the study was to determine the prevalence and zonal distribution of Salmonella serotypes in poultry and to determine the antimicrobial resistance profile of Salmonella isolates. A total of 1,503 cecal samples of poultry were randomly collected from 33 pluck shops across Trinidad. Isolation and identification of Salmonella followed standard methods, and the disk diffusion method was used to determine resistance of isolates to 14 antimicrobial agents. Ninety-one (6.1%) of the 1,503 samples collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…Other studies of the pathogens of poultry in South Africa have similarly reported a high prevalence of MDR in Salmonella isolates in chickens and other livestock, thus highlighting their therapeutic and public health implications [42,[50][51][52][53][54][55][56]. The prevalence of MDR in the current study is higher than was reported, also using the disc diffusion method, for Salmonella from chickens (caeca) in Trinidad, 14.3% [46], Portugal, 75.0% [57], China, 80.0% [58], and in the USA, 92.0% [59], but lower than that reported for isolates in Nepal, 100% [60], Mauritius, 100% [61] and Trinidad, 100.0% [41] and globally [34].…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Other studies of the pathogens of poultry in South Africa have similarly reported a high prevalence of MDR in Salmonella isolates in chickens and other livestock, thus highlighting their therapeutic and public health implications [42,[50][51][52][53][54][55][56]. The prevalence of MDR in the current study is higher than was reported, also using the disc diffusion method, for Salmonella from chickens (caeca) in Trinidad, 14.3% [46], Portugal, 75.0% [57], China, 80.0% [58], and in the USA, 92.0% [59], but lower than that reported for isolates in Nepal, 100% [60], Mauritius, 100% [61] and Trinidad, 100.0% [41] and globally [34].…”
Section: Discussioncontrasting
confidence: 40%
“…Similarly, high prevalence of resistant Salmonella has been reported for chickens slaughtered in the outlets of the 'wet market' in other countries, such as in the cecal contents of chickens slaughtered in 'pluck shops' in Trinidad [46] where 100.0% of the Salmonella isolates were resistant to antimicrobial agents which included 10 of the 16 used in the current study and in India where 100.0% (51/51) of Salmonella isolates from the rectal swabs in poultry exhibited resistance to 16 antimicrobial agents [49].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Suspect typical colonies of Salmonella which were large, glossy black‐centered or almost completely black colonies, were streaked for isolation on blood agar plates and incubated at 37°C for 24 hr to obtain pure cultures. These pure cultures were then used for the identification of Salmonella strains using biochemical tests as earlier described (Khan et al., 2018; Kumar et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Serotyping of Salmonella spp. has been the predominant practice to determine the serotypes and the relatedness of strains recovered from foods, animals, humans, and the environment and during disease investigations in the Caribbean region (Adesiyun, Stewart‐Johnson, & Thompson, 2009; Adesiyun et al., 2014; Buteux et al., 2020, Guyomard‐Rabenirina et al, 2019; Gopee, Adesiyun, & Caesar, 2000; Indar‐Harrinauth et al, 2001; Khan, Georges, Rahaman, Abdela, & Adesiyun, 2018; Kumar, Mohan, Georges, Dziva, & Adesiyun, 2019; Rampersad et al, 1999; Rhynd et al., 2014; Seepersadsingh & Adesiyun, 2003).…”
Section: Introductionmentioning
confidence: 99%